tayyab

5 Reputation

2 Badges

13 years, 233 days

MaplePrimes Activity


These are replies submitted by tayyab

@hirnyk 

i agree its not strong.

@hirnyk 

i agree its not strong.

@Preben Alsholm i have checked it and got the answer. thanks for guidance.

@Preben Alsholm i have checked it and got the answer. thanks for guidance.

i got the result by using your suggestion.  thanks for that.

kindly tell me the purpose of abserr=1e-1 and maxmesh=8192.

what is maxmesh and abserr?

looking forward to your reply.

i got the result by using your suggestion.  thanks for that.

kindly tell me the purpose of abserr=1e-1 and maxmesh=8192.

what is maxmesh and abserr?

looking forward to your reply.

i get the whole programme methodology but in my progrmme 

 

 res := dsolve({ics, ODE1}, numeric, abserr = .1, maxmesh = 8192)              what is maxmesh??

i get the whole programme methodology but in my progrmme 

 

 res := dsolve({ics, ODE1}, numeric, abserr = .1, maxmesh = 8192)              what is maxmesh??

congratulations!!!

it's great. 

you have helped me a lot. i get accurate results.

thanks

with regards

tayyab

you have helped me a lot. i get accurate results.

thanks

with regards

tayyab

thanx tim. it really works.

i hope to also have your help in future.

thanx once again..

thanx tim. it really works.

i hope to also have your help in future.

thanx once again..

i cant define u(x,y) like you have done because its an unknown function.

i have the matrix B as follows

> B := map(diff, A, x);Matrix(3, 3, {(1, 1) = 2*(diff(u(x, y), x, x)), (1, 2) = diff(u(x, y), y, x)+diff(v(x, y), x, x), (1, 3) = 0, (2, 1) = diff(u(x, y), y, x)+diff(v(x, y), x, x), (2, 2) = 2*(diff(v(x, y), y, x)), (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = 0})now i want to multiply it with u(x,y).

i have tried your mentioned procedure more than once the output is

u(x, y) B

it doesnt work.

 

i cant define u(x,y) like you have done because its an unknown function.

i have the matrix B as follows

> B := map(diff, A, x);Matrix(3, 3, {(1, 1) = 2*(diff(u(x, y), x, x)), (1, 2) = diff(u(x, y), y, x)+diff(v(x, y), x, x), (1, 3) = 0, (2, 1) = diff(u(x, y), y, x)+diff(v(x, y), x, x), (2, 2) = 2*(diff(v(x, y), y, x)), (2, 3) = 0, (3, 1) = 0, (3, 2) = 0, (3, 3) = 0})now i want to multiply it with u(x,y).

i have tried your mentioned procedure more than once the output is

u(x, y) B

it doesnt work.

 

Page 1 of 1